The exclusionary rule of illegal evidence in Canadian law - Mohammed Abdullah Al-Zubairii (International Journal of Law Research and Studies, 2024)
The research is concerned with presenting and explaining the rule of excluding illegal evidence in Canadian law, as the Canadian legislator has adopted the legitimacy of accepting any evidence of proof regardless of the legitimacy of obtaining it or not, but has set conditions and restrictions for it, including that it be specific to or related to the dispute presented to the judge, and has given the judge discretionary authority to exclude evidence that has no value in the subject. In the research, we have shown the position of the Canadian legislator on excluding illegal evidence, and it has become clear that in jurisprudence and judiciary, it does not reject illegal evidence completely, but rather has its own conditions for its status, which is to leave the matter of assessing acceptance to the judge, either the evidence is in favor of the case, or the evidence is not important to the case, as the judge’s discretionary power is what determines the extent of acceptance or not, and even if the researcher rejected this opinion due to the waste of the rights stipulated in the constitutions and charters to the extent of preserving the private life of the person and not intruding on it under any name, this opinion has a convincing side when they acknowledged that accepting this evidence despite its illegality saves an innocent person from punishment and protects society from a criminal at large due to the lack of legal conditions in the evidence presented to convict him, even if the whole matter is in the hands of the judge. The research attempted to present this topic in an organized and smooth manner that benefits researchers in this field.
Keywords: Exclusionary Rule; Illegal Evidence; Canadian Law